STRATEGI PEMBELAJARAN MENULIS PARAGRAF ARGUMENTASI BERBASIS SAINTIFIK PADA PESERTA DIDIK SD NEGERI SUNGAI PINYUH - Yuliana, Yuliana (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2018)
Â Learning to write paragraphs of argument in primary schools has not been entrenched because of the lack of interest and motivation of learners to learn to write. The scientific approach in Indonesian language learning especially in writing argumentation is one strategy that can be used to encourage and motivate learners to be more interested in writing an essay of argumentation based on critical and creative thinking. This study aims to describe the implementation of learning to write paragraphs of argumentation with a scientific approach in grade IV primary school. The subjects of this study were classroom teachers, and the fourth grade students at SDN 02, SDN 07 and SDN 08 Sungai Pinyuh. The results of this study indicate that (1) Learning to write paragraphs of argument has been implemented in accordance with the RPP that is designed based on scientific, (2) Learning to write paragraph argumentation has been done by teacher in accordance with scientific step, (3) the teacher has not been skilled in the use of learning resources, (4) Learning outcomes of learners in writing paragraphs argumentation approach scientifically indicate that learners can pour the contents of the idea well.Â Keywords : Writting, Paragraph Argumentation, Saintific Approach